2015
DOI: 10.2174/1874120701509010103
|View full text |Cite
|
Sign up to set email alerts
|

The Kinematics and Kinetics Analysis of the Lower Extremity in the Landing Phase of a Stop-jump Task

Abstract: Large number of studies showed that landing with great impact forces may be a risk factor for knee injuries. The purpose of this study was to illustrate the different landing loads to lower extremity of both genders and examine the relationships among selected lower extremity kinematics and kinetics during the landing of a stop-jump task. A total of 35 male and 35 female healthy subjects were recruited in this study. Each subject executed five experiment actions. Lower extremity kinematics and kinetics were sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
(32 reference statements)
0
7
0
1
Order By: Relevance
“…A power analysis for a regression model based on the kinematic and GRF data from the study of Yin et al. 16 ) indicated that 20 participants would be necessary to attain an a priori power of 0.80. Therefore, 20 healthy male collegiate athletes were recruited.…”
Section: Methodsmentioning
confidence: 99%
“…A power analysis for a regression model based on the kinematic and GRF data from the study of Yin et al. 16 ) indicated that 20 participants would be necessary to attain an a priori power of 0.80. Therefore, 20 healthy male collegiate athletes were recruited.…”
Section: Methodsmentioning
confidence: 99%
“… 7 In the included studies, isokinetic testing angular velocities ranged from 60°/s to 300°/s ( Table 1 ), which are lower than those developed during fast sport movements, such as fast kicking (∼550°/s–1720°/s, 57 sprinting (∼500°/s–800°/s), 58 or landing (∼78°/s–570°/s). 59 , 60 This may also explain the observation that angular velocity does not influence the association of H:Q ratio with injury ( Table 2 ). For this reason, evaluation of the conventional or functional H:Q at a slow angular velocity, such as 60°/s, is recommended.…”
Section: Discussionmentioning
confidence: 89%
“…where, λ = eigen value, I = Identity matrix. Suppose X = A − λI Now, det(X) = λ 2 − 20λ − 6.6354 (29) det(X) is called the characteristic equation of the matrix A. Since the matrix A − λI is singular, det(X) = 0.…”
Section: Resultsmentioning
confidence: 99%
“…Forward dynamics [29] is the connection between the forces applied on a robotic mechanism and the produced accelerations, which is presented in Figure 1. Robot dynamics [30] is the application of rigid-body dynamics to robots.…”
Section: Forward Dynamics Of the Artificial Lower Limb Movementmentioning
confidence: 99%